Contribuições ao estudo da secagem convectiva de concentrado de minério de ferro (pellet feed) - Santos, Lucas Janoni dos (Universidade Federal de São Carlos, 2025)
Iron ore is one of the most important products for Brazilian industry, and is mainly used to produce steel and metallic iron. Given the importance of this product on the national and international scene, the search for new technologies to reduce costs and environmental impacts has become essential in the sector. Part of the extracted ore is processed wet, so subsequent removal of water is essential for the material to be transported and sold. Iron ores with low moisture content can lead to the generation of dust and material losses during transportation. On the other hand, high moisture content has an impact on processing and process efficiency (pelletization), and the Transportable Moisture Limit (TML) must not be exceeded, which limits the maximum moisture content that mineral loads can have to be safely transported in bulk carriers. Therefore, drying becomes an alternative for reducing iron ore moisture when mechanical removal is insufficient to meet these criteria. In this context, the objective of this work was to study the convective drying of iron ore concentrate (pellet feed) at different initial moisture levels and operating conditions to understand the behavior of the material during drying for different saturation states. Correlations for the mass transfer coefficient during drying were also proposed. For this purpose, the material was characterized according to its chemical (Fe > 64%) and mineralogical (75% hematite) composition. Different initial moisture levels affected the aggregation power of the material, with disaggregated material (up to 11% moisture) and agglomerates and sludge (above 12% moisture) being observed. In convective drying, the material with initial moisture levels of 12 and 13% dried completely in the drying chamber for all experimental conditions, which was not observed for the material at 11%, which was dragged with residual moisture until collection in the cyclone underflow. In all experimental conditions, the material retained in the cyclone underflow was lower for higher moisture levels and lower temperatures. Finally, correlations were obtained to predict the mass transfer coefficient in drying for all humidity conditions, obtaining good agreement between the results. These equations can be used in numerical simulations to predict the drying of iron ore concentrate in mineral industry equipment.
Contributions to the study of convective drying of iron ore concentrate (pellet feed)
Keywords: Secagem; Minério de ferro; Pellet feed; Umidade; Drying; Iron ore; Moisture; ENGENHARIAS::ENGENHARIA QUIMICA